2022
DOI: 10.1371/journal.pone.0262738
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies and knowledge, attitude and practice toward COVID-19 in the Republic of Srpska-Bosnia & Herzegovina: A population-based study

Abstract: The aim of the study was to assess the seroprevalence of SARS-CoV-2 in the Republic of Srpska, Bosnia and Herzegovina, and to analyse the knowledge, attitudes and practices of the population toward COVID-19. This population-based study was conducted in a group of 1,855 randomly selected individuals from all municipalities from 1 December 2020 to 15 January 2021. All individuals were asked to sign a consent form and to fill in a questionnaire, following which a blood samples were collected. Total anti-SARS-CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The cause of the increased prescription and consumption of antibiotics is online or telephone consultations, counseling and treatment of COVID-19 cases, especially at the beginning of the pandemic due to the reorganization of the health system. Panic among patients and doctors due to the large number of infected, insufficient knowledge of the clinical course of the disease, the lack of antiviral and immunomodulatory drugs, as well as the low trust of the population in vaccines influenced the excessive use of antibiotics in the observed period [ 30 ]. Also, it is possible that the increased sale of antibiotics without a prescription, although prohibited, has contributed to the overuse of antibiotics, which will certainly affect the rate of antimicrobial resistance, but this is beyond the scope of this paper [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the increased prescription and consumption of antibiotics is online or telephone consultations, counseling and treatment of COVID-19 cases, especially at the beginning of the pandemic due to the reorganization of the health system. Panic among patients and doctors due to the large number of infected, insufficient knowledge of the clinical course of the disease, the lack of antiviral and immunomodulatory drugs, as well as the low trust of the population in vaccines influenced the excessive use of antibiotics in the observed period [ 30 ]. Also, it is possible that the increased sale of antibiotics without a prescription, although prohibited, has contributed to the overuse of antibiotics, which will certainly affect the rate of antimicrobial resistance, but this is beyond the scope of this paper [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of nationwide study in Tunisia showed faster recovering of younger patients as well as healthcare workers [18]. Results of the study on seroprevalence of SARS-CoV-2 antibodies in the Republic of Srpska confirmed that younger population had higher seroprevalence values and less hospitalization [19].…”
Section: Discussionmentioning
confidence: 80%
“…The coronavirus disease 2019 (COVID- 19) is an infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The infection had spread rapidly from China to other countries across the Asia [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody testing was not used to diagnose infection in individuals, nor the amount of protection offered against COVID-19 infection. At the moment, there was no consensus on the best approach used to evaluate COVID-19 infection status in relation to a university community [ 43 , 44 ]. Donneau and colleagues recommended the use of a saliva RT-PCR test and antibody test in conjunction with self-reporting of symptoms in order to determine the prevalence of COVID-19 in the population and characterize seroconversion and seroreversion after vaccination and infection [ 45 ].…”
Section: Discussionmentioning
confidence: 99%